Checklist of Deuteromycetous Fungi of Bangladesh 1 - Shamsi, Shamim (Journal of Bangladesh Academy of Sciences, 2018)
Earlier biodiversity explorations of Bangladesh have led to enumeration of varied flora and fauna. However, fungi being an important biodiversity component, and especially, the mycoflora having potential of impacting human economy and food security, present understanding is needed to make vision for the future. In this regard, past works (1952-2017) on fungi reported from Bangladesh were studied. Two hundred and ten species of anamorphic fungi under 51 genera of the family Dematiaceae are enlisted. The alphabetical checklist of the genera is provided herewith. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 115-126, 2017